The Effectiveness of Mind Mapping Technique on Students' Ability in Writing Procedure Text at The Tenth Grade of MA AL-Falah Tolutu - Rahman, Nur susanti; Hasan, Jhems Richard (English Education Department, 2024)
Writing is an essential skill for students to master in English. One of the texts that students need to learn is procedure text. Procedure text is a text that describes a sequence of actions needed to achieve a goal. However, students often face difficulties in learning to write procedure texts. One common problem is difficulty in explaining the steps. This study aims to determine the effectiveness of using mind mapping techniques to improve students' ability in writing procedure texts. This study uses a quantitative approach with pre-experimental design, one group pretest-posttest design. The sample consists of 19 tenth grade students in MA Al-Falah Tolutu selected through random sampling. Data were collected through tests and questionnaires, then analyzed using paired sample t-test.The results showed an increase in the average value of students' procedure text writing skills before being given treatment (pretest) of 59.94 to 77.76 after being given treatment (posttest). Hypothesis testing obtained sig value. (p-value) of 0,000 <0.05 which means that H0 is rejected and Ha is accepted. Thus, it can be concluded that the mind mapping technique effectively improves students' ability in writing procedure texts. The questionnaire results also showed very good student responses regarding the application of mind mapping techniques in writing procedure texts.